LOGICAL AND SYSTEMATIC GRAND DESIGN OF ROAD MAP FOR SUPER SMART SOCIETY (SOCIETY 5.0) BEYOND INDUSTRY 4.0 - Shinichiro Kawaguchi; Jun Ho Kim; Tseren.G (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
According to the promotion of Super Smart Society (so called Society 5.0)*1 by the Japanese government and Keidanren (Japan Business Federation), Smart Community/City projects are becoming popular, and many cities and communities are challenging this movement. when the government/local authority formulates the grand design of these projects, it becomes common to clarify the necessity of the project and the reason among stakeholders by considering the value created by the project and cost/performance first, and then design a concrete road map including standardization and performance indicators. Under these situation, comprehensive/logical/systematic framework and the deployment of methodology for the grand design of Super Smart Society are indispensable. The aim of this study is to advocate the comprehensive framework and methodology for designing a concrete road map including standardization and KPIs (Key Performance Indicator) for Super Smart Society from the perspective of Organizational Design*2 focused on Smart Community/City. These framework and methodology are helpful for countries to consider promoting Super Smart Society effectively and efficiently.